Enhancement of Production of Exopolysaccharides from Bacillus Species - Vasait, Rajendrabhai Daulatbhai; Laxman, Ahire Vanita; Hemant, Sonawane Pooja; Subhash, Deoghare Neha; Ashok, Borse Archana (Asian Journal of Biological and Life Sciences)
It has been shown that spontaneously synthesized Exopolysaccharides (EPS) are employed for a variety of commercial uses. The kind of EPS generated by bacteria to defend themselves from unsafe circumstances. Food additives as a natural supply of carbohydrates and proteins, bioemulsifiers, stabilizers, biosorbents, cosmetic preparations, anticancer agents, antioxidants, and biologically active antimicrobials are all examples of how EPS is employed. Because EPS generated by bacteria is at a significant commercial level, the current study focused on screening and isolating EPS-producing organisms from the rhizosphere soil of various plants. Four EPS-producing bacteria were isolated and investigated in this study. A medium to enhance EPS production from a Bacillus species, soil isolate, H, was optimized. In order to identify functional groups, FTIR spectrophotometry was employed. Furthermore, the presence of carbohydrates and proteins in EPS was detected subjectively as well as quantitatively. Higher carbohydrate and protein concentrations, such as 23.66 and 15.19 mg/dL, were found in the EPS produced from isolates F and O, respectively. The total protein content of isolate H, EPS was found to be 13.05 g/L. Finally, in presence of optimum conditions, isolate H produced 13.11 g/L of EPS.
Keywords: Bacillus species; Exopolymer.; Exopolysaccharide; Optimization